Ж. Досмұхамедов атындағы педагогикалық колледж студенттерінің көшбасшылық қабілеттерін қалыптастыру - Отарбай, А.Ж. (My University, 2013)
In this report are given the notions such as “Who is a leader?”, “leader’s qualities” “Types of leaders”. Reading this report we can get advices on bringing-up of leaders, and the advices of John Maxwell“ 21 qualities of leader”. The author showed the types of works conducting with the youth for bringing-up leaders, and the results of this work which was done by the organization “Zhaik Youth” in the Pedagogical College after Zh. Dosmukhamedov.